A new eco-friendly mass formulation based on industrial mining residues for the manufacture of ceramic tiles. Issue 8 (15th April 2021) - Almeida, E.P.; Carreiro, M.E.A.; Rodrigues, A.M.; Ferreira, H.S.; Santana, L.N.L.; Menezes, R.R.; Neves, G.A.
Abstract: New eco-friendly mass formulations based on the scheelite and kaolin residues were developed to manufacture ceramic tiles. The start raw materials (scheelite residue, kaolin residue, feldspar and plastic clay) were characterized as to their chemical composition, main mineralogical phases, and particle size distribution. Three ceramic masses with 37 wt% of kaolin residues and different contents of the scheelite residues (2 wt%, 5 wt%, and 10 wt%) were formulated. The mass formulations were uniaxially pressed (19.6 MPa) to obtain samples with dimensions of 60 mm × 40 mm x 7 mm, which were dried at 110 °C/24 h, and sintered at different temperatures (1150 °C, 1200 °C, and 1250 °C). Dilatometric experiments measured thermal expansion coefficients. The results are in agreement with the literature, i.e., 6.0 μm/m°C −1, 6.1 μm/m°C −1 and 6.4 μm/m°C −1 to samples with 2 wt%, 5 wt%, and 10 wt% of scheelite residues, respectively. The potential of the mass formulations studied was evaluated by linear shrinkage, water absorption, apparent density, apparent porosity, flexural strength, and mineralogical phase identification. The results were compared with the literature experimental data and International Technical Standards. It was concluded that the samples investigated have suitable properties for use as ceramic and porcelain tiles. Also, the pseudowollastonite and mullite phases were identified in the sample with the lowest concentration of scheelite residue. These phases are responsible for increasing flexural strength.